Analysis of Factors Related to Levels of Lead in Urine Mechanical Official Workshops in Banjarbaru City Area - Hafiz Al Farizi; Eko Suhartono; Nopi Stiyati Prihatini; Lenie Marlinae (Jurnal Berkala Kesehatan, 2023)
Lead (Pb) is a class of heavy metals that are most commonly used in the motor vehicle industry because lead reacts easily with other compounds. These compounds produce accumulative neurotoxic toxins that are very harmful to the human body. Workshop mechanics are potentially at risk of lead poisoning. Lead can enter the body through absorption mechanisms (respiratory tract, digestion, and skin). Lead is distributed in the body and eliminated 60% through the kidneys then excreted into urine. The purpose of this study was to analyze the factors related to lead levels in the urine of authorized workshop mechanics. This study is a quantitative study with a cross sectional design on 50 respondents of authorized workshop mechanics in Banjarbaru City area by total sampling. Data were analyzed using Spearman Rho test with 95% CI. There was a concentration of lead in the urine of authorized workshop mechanics between 0.024-0.062 mg/L. The results of correlation analysis of age (p-value 0.705), tenure (p-value 0.550) and smoking habits (p-value 0.565) did not have a significant correlation with urine lead levels. There is no relationship between age, length of service and smoking habits on urine lead levels of authorized workshop mechanics in Banjarbaru City area.